Interpretasi cone beam computed tomography 3-dimension dalam pemasangan implan dental di RumahSakit Gigi MulutFakultas Kedokteran Gigi Universitas Padjajaran (Interpretation of cone beam computed tomography 3-dimension in inserting dental implant at Dental Hospital of Faculty of Dentistry Padjajaran University) - Farina Pramanik; Ria N. Firman (DiscoverSys Inc., 2015)
Radiographic examination is one of the examinations required in determining the treatment plan and evaluating thesuccess of dental implant placement. Cone beamcomputed tomography3D(CBCT 3D)is a tool that produce radiographicimaging in three dimensions that can meet the information needed by dentists/specialists in dental implant placement.This report discusses the role of interpretating the CBCT 3D bone area, indication of dental implant with give a sight3D, measure the distance and position of the implant and to assess the quality of the bone at dental implant placement.Interpretation of CBCT 3D case is the size of the dental implant alveolar bone morphometric teeth region 46 and 37qualified radiographically for dental implants. The conclusion of this paper is a CBCT 3D can be a determinant of thesuccess of dental implant placement as capable of being able to analyze a complete, clear and more accurate measurementthrough a 3D picture, the analysis of the size/3D morphometric, density analysis, and histogram/ trabecular analysis.